EFFECTIVENESS OF WALKING EXERCISE ON HBA1C AND BMI OF DIABETES MELLITUS TYPE 2: A SYSTEMATIC REVIEW - Fitri, Nurul; Dewi, Yulis Setiya; Suarilah, Ira; Efendi, Cahyaningsih; Yazid, Syahrul Abdul (Nurse and Health: Jurnal Keperawatan, 2024)
Background : Survey data shows that there are 51.9% of DM sufferers who do not exercise as an alternative to controlling diabetes. Walking exercise has been demonstrated to have an impact on BMI and HbA1c in one trial, but only in people with prediabetes. Objective: Analyzed the results of primary research regarding the effectiveness of walking exercise in controlling the HbA1c and body mass index (BMI). Methods: Design of this study was a systematic review. Data sources of this article was from 4 databases (Scopus, EBSCO, Proquest and Pubmed). Search for articles for the last 10 years, Mar 2015- Mar 2024. The research method used PRISMA 2020 guidelines. Article selection used the PICO framework. Medical Subject Heading (MeSH) is used to search for keywords. The quality assessment of an article is assessed using the Joanna Briggs Institute (JBI) format. Results: Walking exercise has a positive effect on HbA1c and BMI. Four of the eight articles showed a significant effect of walking exercise on reducing HbA1c. Three of the 7 articles showed a significant effect of walking exercise on reducing BMI. Conclusion: Walking exercise is a type of physical exercise that is considered to have a positive effect on body health for both diabetics and non-diabetics. Walking exercise can improve the metabolic status of diabetes sufferers by reducing blood glucose levels, HbA1c and BMI.